Mapping of social initiatives as a model of local development against depopulation in rural areas. The Valle del Genal case (Andalusia, Spain) - Rosa-Jiménez, Carlos; Márquez-Ballesteros, María José; García-Moreno, Alberto Enrique; Arjones-Fernández, María Aurora; Chamizo-Nieto, Francisco José; Galacho-Jiménez, Federico Benjamín; Reyes-Corredera, Sergio Jesús; Nebot-Gómez-de-Salazar, Nuria; Conejo-Arrabal, Francisco; Pérez-Belmonte, Rubén; Salgado-Alcaraz, Salvador (My University, 2022)
The cultural heritage of many rural areas, such as the villages of Valle del Genal in Andalusia, is endangered. Factors such as the depopulation suffered in the last 25 years have prevented the knowledge transfer from the elderly to the young. This paper focuses on mapping the social, economic and habitat resources as a preliminary step to the implementation of measures and policies against the abandonment of these areas. The aim is to create a map regarding the cultural identity and idiosyncrasy of each village in the valley. The mapping of these local entities is carried out through a combination of participatory work with the communities in the area and the data tracking from geo-positioning and social networks applications. During the identification and inventory process, the relationship between different citizen initiatives and social groups are analysed. This cartography pretends to offer a base of accessible knowledge for inhabitants and visitors.
Keywords: Población rural; Valle del Genal; Rural environments; Depopulation; Social mapping; Participatory work; GIS platform